Americans do not select their doctors based on race - Olinger, Reilly; Matejka, Benjamin; Chakravarty, Rohan; Johnston, Margaret; Ornelas, Eliana; Draves, Julia; Jain, Nishi; Hentschel, Jane; Owen, William; Ma, Yuchuan; Marx, William; Freitag, Joshua; et al. (Frontiers in Sociology, 2024)
To what extent do Americans racially discriminate against doctors? While a large literature shows that racial biases pervade the American healthcare system, there has been no systematic examination of these biases in terms of who patients select for medical treatment. We examine this question in the context of the ongoing global COVID-19 pandemic, where a wealth of qualitative evidence suggests that discrimination against some historically marginalized communities, particularly Asians, has increased throughout the United States. Conducting a well-powered conjoint experiment with a national sample of 1,498 Americans, we find that respondents do not, on average, discriminate against Asian or doctors from other systematically minoritized groups. We also find no consistent evidence of treatment effect heterogeneity; Americans of all types appear not to care about the racial identity of their doctor, at least in our study. This finding has important implications for the potential limits of American prejudice.